Small intestinal intussusceptions due to the placement of a percutaneous endoscopic jejunostomy tube. (20th January 2011) - Satoh, Takayuki; Sawada, Kazue; Satoh, Miyuki; Yohko, Kikuchi; Yamada, Masataka; Zaitsu, Masaaki; Osada, Tadahiro; Sawaya, Reiji; Nata, Toshie; Ueno, Nobuhiro; Moriichi, Kentaro; Ikuta, Katsuya; et al.
Abstract : Percutaneous endoscopic jejunostomy (PEJ) has been developed and is considered to be a better method than percutaneous endoscopic gastrostomy for preventing the occurrence of aspiration pneumonia. However, the incidence of other complications associated with this procedure is less clear. We herein report a rare case with a small intestinal intussusception due to a PEJ placement. In this case, a radiologic examination with gastrografin was useful to detect the typical findings of a small intestinal intussusception, a beak-like filling defect, and identify the location of the lesion. An endoscopic examination that was carefully performed with a thin scope was effective to observe the ischaemic change of the small intestine and immediately determine the indication for surgical treatment. This case highlights the necessity to carefully manage patients with a PEJ placement, considering the risk of small intestinal intussusceptions when the patient complains of symptoms that are suspicious for an intestinal obstruction.